2005
DOI: 10.1080/10236240400029366
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, development, and metabolism of larval stages of the warmwater shrimp,Caridina babaulti basrensis(Decapoda, Atyidae)

Abstract: Peak release of zoea I larvae of the warmwater shrimp, Caridina babaulti basrensis (Al-Adhub AHY 1987) in the field coincided with the highest summer water temperature (33 C). Zoea I abundances did not correlate significantly with the phase of the lunar cycle ( p ¼ 0.256) and only slightly with time of day (day : night regimes, p ¼ 0.079). Temperature correlated significantly with zoeae I larval release in the field ( p < 0.0001). Development and respiration were measured at constant water temperatures ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The relation of the rate of O2 consumption of the barnacle B.a.amphitrite follow the normal pattern of increase with increasing temperature and body weight, and this concur with the results of Dame (1976); Al-Dabbagh and Marina (1986); Idrisi and Salman (2005); Abdullah (1996) The present results showed that the b values of the relationships of metabolism at 15, 23 and 30 °C were -0.623,-0.676 and -0.520, respectively which are lower than the b value of B. balanoides (-0.77) at 15 °C (Newell and Northeroft ,1967), and more than those of B. balanoides and B. balanus reported by Barnes and Barnes (1969) (-0.388 at 15 °C and -0.327 at 20 °C for the former and -0.4204 at 15 °C and -0.2145 at 20 °C, for the latter). Moreover, the present results indicate that B.a.…”
Section: Discussionsupporting
confidence: 87%
“…The relation of the rate of O2 consumption of the barnacle B.a.amphitrite follow the normal pattern of increase with increasing temperature and body weight, and this concur with the results of Dame (1976); Al-Dabbagh and Marina (1986); Idrisi and Salman (2005); Abdullah (1996) The present results showed that the b values of the relationships of metabolism at 15, 23 and 30 °C were -0.623,-0.676 and -0.520, respectively which are lower than the b value of B. balanoides (-0.77) at 15 °C (Newell and Northeroft ,1967), and more than those of B. balanoides and B. balanus reported by Barnes and Barnes (1969) (-0.388 at 15 °C and -0.327 at 20 °C for the former and -0.4204 at 15 °C and -0.2145 at 20 °C, for the latter). Moreover, the present results indicate that B.a.…”
Section: Discussionsupporting
confidence: 87%
“…Almeida et al (2010) also collected ovigerous females of Atya scabra throughout the entire year, characterizing the reproduction as continuous. The breeding period in the Atyidae family demonstrated to be continuous in many studies (Benzie & De Silva, 1988;De Silva, 1990;Idrisi & Salman, 2005;Leuven, Van Der Brink, & Van Der Velde, 2008). It is possible that the rainy season is able to influence peaks (Hoarau, 2018;Hoffman & Negreiros-Fransozo, 2010).…”
Section: Discussionmentioning
confidence: 99%